2019
DOI: 10.1039/c9cp04156g
|View full text |Cite
|
Sign up to set email alerts
|

Dendronised Ni(ii) porphyrins as photoswitchable contrast agents for MRI

Abstract: On–off photoswitching of MRI contrast in water and gels with spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…In order to check whether the switching efficiencies would decrease in aqueous environment to a similar extend as in previous cases [ 3 ], switching experiments with the protic record players 1e (R = OH), 1h (SH) and 1j (R = COOH) in acetone/water 1:9 were performed. UV experiments revealed that the switching efficiencies of the protonated species indeed dropped dramatically as compared to those in pure acetone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to check whether the switching efficiencies would decrease in aqueous environment to a similar extend as in previous cases [ 3 ], switching experiments with the protic record players 1e (R = OH), 1h (SH) and 1j (R = COOH) in acetone/water 1:9 were performed. UV experiments revealed that the switching efficiencies of the protonated species indeed dropped dramatically as compared to those in pure acetone.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). If it comes to medical applications, such as switchable contrast agents [ 3 – 7 ], the new carboxylate substituted system 1j has the distinct advantage of being deprotonated at neutral pH, whereas the previously synthesized hydroxylate system 1e exhibits its highest switching efficiency at unphysiological pH 10.5 [ 14 ]. Hence, further attempts to optimize our molecular spin switches will be based on pyridine-4-carboxylate-substituted systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several light-responsive MRI CAs have been reported in the last decade. For instance, Herges and co-workers reported porphyrin-based nickel(II) complexes, bearing a photoresponsive azobenzene moiety, whose relaxivity can be switched on by irradiation with λ = 505 nm light [ 22 , 23 ]. Even though the authors were able to minimize initial challenges with respect to the low water solubility, the overall very low relaxivity (0.03 s −1 mM −1 at 7T) remains a challenge [ 24 ].…”
Section: Introductionmentioning
confidence: 99%